CREOLISATION (PATWA) AND THE CARIBBEAN NOVEL: GRAMMATICAL AND STYLISTIC ANALYSIS OF SAMUEL SELVON’S THE LONELY LONDONERS AND V. S. NAIPAUL’S THE SUFFRAGE OF ELVIRA - MBU, Dora Nyuykighan; NSAIRUN, Theodore Shey (International Journal of Arts, Languages, Linguistics and Literary Studies, 2025)
This paper examines the grammatical structures and literary stylistic manifestations, forms, and features of Creole in Samuel Selvon’s The Lonely Londoners and V. S. Naipaul’s The Suffrage of Elvira. Though the identity of Creole manifests at all levels of language structure, using the functional theories of grammar with emphasis on the human need-contact theory, "Creole hypothesis”, and Creolisation, an attempt is made to itemize the striking occurrences and usages of Creole in ways that differ in forms and functions from Standard English usage. Findings from extracts in the novels suggest that striking linguistic features such as lexicology, subject-verb and tense agreement, and other literary features, serve specific communicative roles that give insights into why Selvon and Naipaul have explored them as an indigenous style of writing in these texts.